2022
DOI: 10.1111/tpj.15872
|View full text |Cite
|
Sign up to set email alerts
|

mRNA N6‐methyladenosine is critical for cold tolerance in Arabidopsis

Abstract: Plants respond to low temperatures by altering the mRNA abundance of thousands of genes contributing to numerous physiological and metabolic processes that allow them to adapt. At the post-transcriptional level, these cold stress-responsive transcripts undergo alternative splicing, microRNA-mediated regulation and alternative polyadenylation, amongst others. Recently, m 6 A, m 5 C and other mRNA modifications that can affect the regulation and stability of RNA were discovered, thus revealing another layer of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 77 publications
4
57
1
Order By: Relevance
“…R = A/G; W = A/U; K = G/U; Y = C/U; D = A/G/U; H = A/C/U; V = A/G/C. b m 6 A modifications are influenced by various endogenous and environmental signals as shown in the following studies: developmental stages (strawberry [ 117 ], wheat [ 125 ]); different organs ( Arabidopsis [ 137 ]); ecotype divergence ( Arabidopsis [ 138 ]); blue light ( Arabidopsis [ 79 ]); salt stress ( Arabidopsis [ 139 , 140 ], sweet sorghum [ 128 ], rice [ 141 ], sugar beet [ 142 ], cotton [ 133 ]); heat/low temperature (pak-choi [ 122 ], Arabidopsis [ 143 ], tomato [ 124 ]); cadmium stress (rice [ 127 ], barley [ 132 ]); drought stress (sea-buckthorn [ 118 ], populus [ 119 ], apple [ 135 , 144 ]); pathogen infection (apple [ 108 ], rice [ 145 ], wheat [ 126 ], watermelon [ 131 ], pear [ 116 ]); and nematode infection (soybean [ 146 ]). c Expression of m 6 A writer and eraser genes are modulated by multiple external stimuli in Arabidopsis .…”
Section: Advances In Landscape and Regulation Of Plant M 6 ...mentioning
confidence: 99%
“…R = A/G; W = A/U; K = G/U; Y = C/U; D = A/G/U; H = A/C/U; V = A/G/C. b m 6 A modifications are influenced by various endogenous and environmental signals as shown in the following studies: developmental stages (strawberry [ 117 ], wheat [ 125 ]); different organs ( Arabidopsis [ 137 ]); ecotype divergence ( Arabidopsis [ 138 ]); blue light ( Arabidopsis [ 79 ]); salt stress ( Arabidopsis [ 139 , 140 ], sweet sorghum [ 128 ], rice [ 141 ], sugar beet [ 142 ], cotton [ 133 ]); heat/low temperature (pak-choi [ 122 ], Arabidopsis [ 143 ], tomato [ 124 ]); cadmium stress (rice [ 127 ], barley [ 132 ]); drought stress (sea-buckthorn [ 118 ], populus [ 119 ], apple [ 135 , 144 ]); pathogen infection (apple [ 108 ], rice [ 145 ], wheat [ 126 ], watermelon [ 131 ], pear [ 116 ]); and nematode infection (soybean [ 146 ]). c Expression of m 6 A writer and eraser genes are modulated by multiple external stimuli in Arabidopsis .…”
Section: Advances In Landscape and Regulation Of Plant M 6 ...mentioning
confidence: 99%
“…We first arranged these 79 recovered transcripts according to their differential expression, from up‐ to downregulated (33 and 46 mRNAs, respectively). When we observed the extent of methylation in each mRNA (as defined by the P ‐value), there was no clear association between this value and the direction of changes in mRNA accumulation (Figure 5a), suggesting that additional factors determine the fate of the m 6 A‐containing transcripts to direct them to down‐ or upregulation, as described in other biological systems (Frye et al., 2018; Ivanova et al., 2017; Wang et al., 2021), including plants (Anderson et al., 2018; Govindan et al., 2022). Among these 79 m 6 A‐DE transcripts we identified factors involved in the development of buds, for instance PpAPB2 (Pp3c9_25570) (Aoyama et al., 2012), and others related to auxin signaling, such as the ARF domain protein (Pp3c6_21370V3.1) and the AUX/IAA domain factor (Pp3c15_9710V3.1), which are methylated and downregulated in Ppmta plants (indicated by aqua asterisks in Figure 5a,c; Figure S7).…”
Section: Resultsmentioning
confidence: 90%
“…By applying meme algorithms to identify potential methylation sequence motifs enriched in these regions, we found a 7‐nt sequence with the consensus GRAGRAG (where R = A/G, P = 9.1e‐056; Figure 4c). Previous reports have shown that in plants the methylation motif RRACH has undergone diversification, and furthermore, depending on the tissue, growth conditions or environmental stimuli, the modified mRNAs exhibit different consensus motifs (Anderson et al., 2018; Govindan et al., 2022; Zhou et al., 2022). Here, we propose GRAGRAG as a methylation motif present in P .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations